Shaping Resilient Faith through Sto. Niño Bendisyoni Hymn: The Case of Local Parishioners in Tacloban City - Ma. Cassandra L. Alag; Francelle Jonah D. Globio; Regina Claire C. Diaz; Martin Jeo Manog; Jay P. Mabini (Future Science / FSH-PH Publications, 2026)
This study explored the role of the Sto. Niño Bendisyoni hymn in shaping and sustaining resilient faith among local parishioners in Tacloban City, a community deeply affected by the trauma of Super Typhoon Yolanda. Utilizing a qualitative single case study design, the researchers conducted in-depth interviews with long-term parishioners to examine how this locally revered hymn reinforces spiritual strength, communal identity, and emotional healing. Findings revealed that the hymn functions not only as a liturgical tradition but also as a spiritual anchor that inspires hope, unity, and a profound connection to the divine, especially during times of crisis. Participants described the hymn as a “musical prayer” that fosters both personal and collective resilience, underscoring its importance in their daily worship and cultural identity. Grounded in Fowler’s Faith Development Theory, this study affirms that sacred music, particularly the Sto. Niño Bendisyoni hymn, serves as a transformative medium for faith formation and community recovery, highlighting its enduring power in post-disaster spiritual life.